2020
DOI: 10.1002/pon.5502
|View full text |Cite
|
Sign up to set email alerts
|

Psychological aspects of gestational cancer: A systematic review

Abstract: Objective: Gestational cancer is defined as any type of cancer diagnosed during pregnancy or within 12 months of delivery. To date, existing studies on the psychological aspects of this type of cancer have not been evaluated for methodological quality. The aim of this systematic review was to identify the psychological aspects of gestational cancer. Methods: Five journal databases were searched to identify peer-reviewed articles reporting upon the psychological aspects of women with gestational cancer. Studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 54 publications
2
25
0
1
Order By: Relevance
“…Similar mood changes were observed in women diagnosed with cancer in pregnancy: 51.5% of pregnant women were clinically distressed, while the distress was mostly experienced as intrusive thoughts [ 92 ]. Positive coping strategies were associated with decreased level of concern [ 112 ]. Vandenbroucke et al reported a high level of distress (in both parents) related to concerns regarding the child’s health, the cancer diagnosis and treatment, the outcome of the pregnancy and the delivery [ 113 ].…”
Section: Psychological Impact Of Cancer In Pregnancymentioning
confidence: 99%
See 3 more Smart Citations
“…Similar mood changes were observed in women diagnosed with cancer in pregnancy: 51.5% of pregnant women were clinically distressed, while the distress was mostly experienced as intrusive thoughts [ 92 ]. Positive coping strategies were associated with decreased level of concern [ 112 ]. Vandenbroucke et al reported a high level of distress (in both parents) related to concerns regarding the child’s health, the cancer diagnosis and treatment, the outcome of the pregnancy and the delivery [ 113 ].…”
Section: Psychological Impact Of Cancer In Pregnancymentioning
confidence: 99%
“…Vandenbroucke et al reported a high level of distress (in both parents) related to concerns regarding the child’s health, the cancer diagnosis and treatment, the outcome of the pregnancy and the delivery [ 113 ]. During the ongoing pregnancy, nulliparous women showed more concerns than multiparous, and in general, women were concerned about the effects of the chemotherapy on the progeny [ 112 ]. Pregnant women tended to overestimate the impact of antenatal chemotherapy on short-term and long-term effects on the offspring [ 112 ].…”
Section: Psychological Impact Of Cancer In Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…The role of comprehensive cancer care coordination in optimizing patient outcomes is recognised in Australia[7], but there is little research within the context of GC. The limited information available suggests that meeting the challenges of the complexity of care inherent in this group is central to perceived quality of care and wellbeing [4,14,15]. No previous study has investigated the experiences of the HPs treating this population; perspectives which are needed to better understand the barriers to comprehensive GC care.…”
Section: Introductionmentioning
confidence: 99%